Antibiotic prescribing practices in periodontal surgeries with and without bone grafting. Issue 4 (23rd August 2019) - Hai, Justine Hoda; Lee, Cliff; Kapila, Yvonne L.; Chaffee, Benjamin W.; Armitage, Gary C.
Abstract: Background: The prevention of postoperative infection is often the basis for antibiotic prescription; however, the risks of unwarranted antibiotics and lack of guidelines for procedures involving bone grafts creates additional difficulty in decision making for practitioners. This study aims to evaluate practices in antibiotics prescribed for periodontal surgeries with and without bone grafting and acceptability of guidelines. Methods: An anonymous survey was distributed to periodontists via the California Society of Periodontists e‐mail listserv. The survey questioned prescribing practices for periodontal procedures, prescribing rationale, demographic and dental practice information, and acceptability of guidelines. Results were analyzed using McNemar tests and logistic regression. Results: Practitioners were significantly less likely to prescribe antibiotics for traditional periodontal surgeries without bone grafting compared with socket preservation, guided tissue regeneration, guided bone regeneration, and sinus augmentation ( P < 0.0001). Practitioners were significantly more likely to prescribe antibiotics with more complex bone grafting such as guided bone regeneration and sinus augmentation compared with socket preservation ( P  < 0.0001). The most common rationale for prescribing antibiotics with bone grafting was to decrease the chances of developing an infection. Seventy‐five percent of practitioners reported they would follow guidelines for antibiotic prescription if they were developed by the American Academy of Periodontology. Conclusions: Practitioners are more likely to prescribe antibiotics with bone grafting and as complexity of the bone grafting procedure increases. Based on these results, the low incidence of infection in periodontal surgery cited in the literature, and willingness of practitioners to adopt guidelines, the establishment of evidence‐based guidelines would be of benefit to the periodontal practicing community.